Quantitative Hedge Fund Selection (Part 2) - TEO, Melvyn (Institutional Knowledge at Singapore Management University, 2011)
Do fund incentives, volatility exposure, and liquidity risk affect fund performance? We show that hedge funds with high performance fees and high water mark provisions tend to outperform those with low performance fees and no high water marks. Moreover, funds that short volatility and embrace liquidity risk deliver significantly higher returns relative to funds that long volatility and eschew liquidity risk. Investors with access to secure capital and managed account platforms may be positioned to take advantage of these performance differences.